Mild Allergic Transfusion Reactions: Impact of Associated Clinical Symptoms?. Issue 3 (13th November 2018) - Adkins, Brian D; Lawicki, Shaun; Johnson, Mary; Eichbaum, Quentin
Abstract: Objectives: Transfusions are often needlessly aborted after occurrence of a mild allergic transfusion reaction (ATR), leading to wastage and reexposure of recipients to additional blood products (with potential alloimmunization). We aimed to determine the symptoms associated with such reactions (along with other parameters) as a possible reason of concern for transfusionists aborting such transfusions. Methods: We reviewed the symptomology of all mild ATRs (as well as the associated wastage and costs of aborted transfusions) at an academic medical center that occurred over a period of 1 year. Results: Of the patients, 52.3% had nonatopic-associated symptoms. The most common associated symptom was tachycardia (37.8%), followed by dyspnea (28.9%), hypotension (17.8%), and hypertension (13.3%). More than half of patients (54.7%) required retransfusion. The estimated cost of product wastage was 12, 507. Conclusions: Understanding symptoms associated with mild ATRs may lead to improved management of patients, with fewer unnecessary transfusions and less wastage.